EFEKTIVITAS PEMBELAJARAN BAHASA INDONESIA DALAM SISTEM DARING KELAS IV UPT SDN 24 GRESIK - Agam Alfisila; Afakhrul Masub Bakhtiar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Learning effectiveness is a measure of the success of a process of interaction between students and between students and teachers in educational situations to achieve learning objectives. The development of children's learning will greatly depend on whether the process of teaching and learning activities (KBM) delivered by the teacher is good or not. The development of children's learning at home during the Covid-19 pandemic will tend to be different from the development of learning at school so that the teacher as a facilitator must have various innovations, to provide motivation to students in carrying out teaching and learning activities (KBM). The type of research that the authors use is a qualitative approach which uses descriptive analysis through field research with the aim of describing the effectiveness and barriers to learning Indonesian in the online system for class IV. The results showed that the implementation of learning Indonesian with an online system in class IV was less effective because in practice students were only given questions and only occasionally practiced, and the teacher did not know whether students really understood or not. Bearing in mind that students while studying at home are accompanied by parents or guardians of students, so it is possible that student assignments are assisted by parents or guardians of students. There are several obstacles that occur in online learning, namely teachers cannot know the extent to which students' abilities are, and also parents' finances differ in providing learningtools